2021
DOI: 10.3390/jpm11020073
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Expression Is Associated with Deficient Mismatch Repair and Poor Prognosis in Middle Eastern Colorectal Cancers

Abstract: Several clinical trials are investigating the use of immune-targeted therapy with Programmed death ligand-1 (PD-L1) inhibitors for colorectal cancer (CRC), with promising results for patients with mismatch repair (MMR) deficiency or metastatic CRC. However, the prognostic significance of PD-L1 expression in CRC is controversial and such data are lacking in CRC from Middle Eastern ethnicity. We carried out this large retrospective study to investigate the prognostic and clinico-pathological impact of PD-L1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Tissue microarray (TMA) format was utilized for immunohistochemical analysis of samples. Construction of TMA was done as described previously 28 . Briefly, representative tumor regions from each donor tissue block were chosen and tissue cylinders with a diameter of 0.6 mm were punched and brought into recipient paraffin block with the help of a modified semiautomatic robotic precision instrument (Beecher Instruments, Wood-land, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue microarray (TMA) format was utilized for immunohistochemical analysis of samples. Construction of TMA was done as described previously 28 . Briefly, representative tumor regions from each donor tissue block were chosen and tissue cylinders with a diameter of 0.6 mm were punched and brought into recipient paraffin block with the help of a modified semiautomatic robotic precision instrument (Beecher Instruments, Wood-land, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, PD-L1 expression is found in only 9–15% of CRC patients [ 96 ]. Reports showed that upregulation of PD-L1 in CRC cells is associated with poorly differentiated and solid/medullary histology, MSI-H or dMMR, and BRAF mutations [ 95 , 97 , 98 ], signatures of the serrated neoplasia pathway of colorectal adenocarcinomas [ 99 ]. In tissue samples collected from 43 patients with colon cancer, Cen et al found that BRAF mutation colon cancer had significantly higher expression of PD-L1, PD-1, CTLA4, LAG3, and TIM3, which is consistent with data from 396 colon cancers from TCGA datasets [ 85 ].…”
Section: Potential Biomarkers In the Tumor Immune Microenvironment Fo...mentioning
confidence: 99%
“…PD‐L1 is expressed at different levels in various cancers and is associated with poor prognosis in melanoma, 6 NSCLC 7 and colorectal cancer. 8 However, the clinical implications of PD‐L1 expression vary across studies. The Pembrolizumab trial found that patients with ≥1% PD‐L1 expression had significantly better survival.…”
Section: Introductionmentioning
confidence: 99%
“…PD‐L1 (CD274 gene) is upregulated in many cell types, including cancer cells, in response to pro‐inflammatory cytokines. PD‐L1 is expressed at different levels in various cancers and is associated with poor prognosis in melanoma, 6 NSCLC 7 and colorectal cancer 8 . However, the clinical implications of PD‐L1 expression vary across studies.…”
Section: Introductionmentioning
confidence: 99%